Decreased Subcutaneous Adipose Tissue Correlates With Higher Portal Hypertension and Poor Survival in Patients With Cirrhosis: A Retrospective Binary-Center Study - Yang, Siwei; Ren, Xiuwan; Guo, Xiaoqing; Yu, Jianan; Niu, Lizhen; Niu, Yao; Zhang, Linpeng; Jin, Long (Clinical and translational gastroenterology, 2025)
INTRODUCTION:The aim of this study was to investigate the impact of hepatic venous portal gradient (HVPG) on body composition (BC) values and the prognostic value of BC value in cirrhotic patients.METHODS:A total of 173 cirrhotic patients with HVPG and computed tomography scan were screened retrospectively from a binary-center database. Seven BC values, including skeletal muscle index, subcutaneous adipose tissue index (SATI), deep SATI (dSATI), superficial SATI (sSATI), visceral adipose tissue index, and ratio of visceral adipose tissue index and SATI along with skeletal muscle radiodensity, were analyzed. The correlation analyses and multiple linear regression were used to assess the impact of HVPG on BC values. The cumulative survival rate was assessed, and risk factors of survival were identified by competing risk analysis using Fine-Gray model.RESULTS:Among 173 patients with a mean age of 53.7 ± 10.5 years, there were 111 male patients (64.2%) and 62 female patients (35.8%). In male patients, SATI, dSATI, and sSATI inversely correlated with HVPG, respectively (SATI: rho = −0.227; dSATI: rho = −0.229; sSATI: rho = −0.219; all P < 0.05), especially in patients aged 60 years or younger or with compensated cirrhosis; male patients with clinically significant portal hypertension had a lower SATI, dSATI, sSATI, and skeletal muscle radiodensity than those without clinically significant portal hypertension. After adjusted multiple linear models, male sex, Child-Pugh class B or C, and elevated HVPG contributed to decreased SATI. Multiple competing survival analysis showed a lower SATI (male: <38 cm2/m2; female: <23 cm2/m2), and Child-Pugh B or C predict mortality.DISCUSSION:Decreased SATI, dSATI, and sSATI were more closely associated with increased HVPG. A lower SATI and Child-Pugh B or C predicted mortality.